Life-story method utilisation for professional development of high school counselors in Slovenia - Kokol, Katja (Psihološka obzorja (Ljubljana), 2022)
This article researches the professional development of trained psychologists (holding a bachelor’s degree in Psychology) that work as school counsellors in Slovenia utilising the life-story method. Using the Case Study methodology on four examples, it tries to determine which factors, they deem important for their professional development and how they explain the influence of those factors on their work. The professional development factors were then categorised based on recognising similarities in school counsellors’ life-stories, dividing them into areas: (first and second phase) university education, preparation for professional work, work climate, relationships with co-workers, stress & burnout and protective factors & work motivation. Results of our study mostly correspond with previous studies and show that school counsellors work is diverse and often stressful.
Keywords: motivacija; poklicna biografija; poklicni razvoj; srednje šole; stres; svetovalni delavci; šolsko svetovalno delo